2012
DOI: 10.3109/03639045.2012.657644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmaceutical excipients on the stability of angiotensin-converting enzyme inhibitors in their solid dosage formulations

Abstract: Magnesium stearate and increased relative humidity induce MOXL instability, while glyceryl behenate is an optimal lubricant, and therefore, it is recommended for moexipril-containing solid formulations. However, for the formulations containing moexipril and magnesium stearate, it is suggested to minimize the humidity level during storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Stability studies have received considerable attention in recent years because of their importance in the development and quality control of pharmaceutical products [25][26][27][28][29][30][31][32][33][34][35] . They make part of a development strategy under ICH requirements and should be carried out to establish the inherent or intrinsic stability characteristics of the molecule in a variety of suggested degradation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Stability studies have received considerable attention in recent years because of their importance in the development and quality control of pharmaceutical products [25][26][27][28][29][30][31][32][33][34][35] . They make part of a development strategy under ICH requirements and should be carried out to establish the inherent or intrinsic stability characteristics of the molecule in a variety of suggested degradation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…They can help increase the solubility/compatibility/patient acceptability of the API and help maintain the physicochemical stability of the API in the formulated products. [1][2][3][4] A number of excipients with diverse functions are frequently used in vaginally administered drug products, including the vaginal microbicides tested in preclinical and clinical studies for topical preexposure prophylaxis (PrEP) of sexually transmitted HIV-1. [5][6][7][8] In the design and development of vaginal formulations, the effect of formulation ingredients on the integrity of the cervicovaginal epithelium should be carefully evaluated.…”
mentioning
confidence: 99%
“…Results obtained by the proposed method for the determination of pure samples of MOX and MOXT are statistically compared to those obtained by the reported methods 4 . The calculated t and F values were found to be less than their corresponding theoretical ones confirming good accuracy and excellent precision (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that MOX was identified by HPLC [4][5][6], spectrophotometry [7,8], gas chromatography mass spectrometry [9], and liquid chromatography tandem mass spectrometry [10,11]. In 2006, Koti, J. et al developed a LC-MASS spectrometry method just to monitor the metabolism of MOX to MOXT [10].…”
Section: Moexipril (3s)-2-[(2s)-2-[[(1s)-1-(ethoxycarbonyl)-3-phenylpmentioning
confidence: 99%
See 1 more Smart Citation